Analysis the impact of boycott pro-Israel products on the financial performance of multinational companies in Indonesia - Syarif Maula Andriansyah; Uray Ndaru Mustika; Mustarudin; M. Irfani Hendri (Forum Kerjasama Pendidikan Tinggi, 2025)
This research seeks to examine the effects of the boycott against pro-Israel products on the financial performance of multinational companies in Indonesia. Boycotts of pro-Israel products are often triggered by political and social factors, which can affect consumer perceptions and purchasing behaviour. This study utilizes a quantitative approach by analyzing secondary data obtained from the financial statements of Indonesian companies whose pruducts were affected by the boycott, both before and following the expansion of the boycott within Indonesia. The findings of the research suggest that the decision to reject products originating from Israel or associated with Israeli entities significantly affects the financial outcomes of various multinational corporations in Indonesia, particularly those with a substantial presence in markets of nations that endorse the boycott. The impact is seen in decreased sales, decreased stock prices, and decreased profitability. This study provides important insights for issuers in Indonesia in anticipating and responding to product boycotts and their implications for their financial performance.